2019
DOI: 10.3390/nu11071633
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota, Muscle Mass and Function in Aging: A Focus on Physical Frailty and Sarcopenia

Abstract: Human gut microbiota is able to influence the host physiology by regulating multiple processes, including nutrient absorption, inflammation, oxidative stress, immune function, and anabolic balance. Aging is associated with reduced microbiota biodiversity, increased inter-individual variability, and over-representation of pathobionts, and these phenomena may have great relevance for skeletal muscle mass and function. For this reason, the presence of a gut-muscle axis regulating the onset and progression of age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
209
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(250 citation statements)
references
References 142 publications
3
209
1
11
Order By: Relevance
“…Although our investigation does not provide mechanistic elements to support such a hypothesis, the relevance of systemic inflammation to PF&S has previously been shown [11]. From this perspective, systemic inflammation would represent one of the effectors of the "gut-muscle axis" that has recently been proposed to contribute to the development of PF&S [23,63,67].…”
Section: Discussionmentioning
confidence: 70%
“…Although our investigation does not provide mechanistic elements to support such a hypothesis, the relevance of systemic inflammation to PF&S has previously been shown [11]. From this perspective, systemic inflammation would represent one of the effectors of the "gut-muscle axis" that has recently been proposed to contribute to the development of PF&S [23,63,67].…”
Section: Discussionmentioning
confidence: 70%
“…Recent studies have suggested that Bifidobacterium is recognized as a key taxon for physical frailty and sarcopenia in elderly individuals [8]; however, it remains unclear whether the decreases in bifidobacterial abundance that occur with age influence muscle health [7,41]. The present study explored the positive relationships between Bifidobacterium and muscle health.…”
Section: Discussionmentioning
confidence: 95%
“…Accumulating evidence has indicated that gut microbiota are associated with host health conditions in numerous ways [4], including through energy metabolism and mitochondrial function [5,6]. Moreover, the cross-talk pathway between the gut microbiota and skeletal muscle, i.e., the gut-muscle axis, has been extensively studied, and microbiota composition and the intestinal environment have been suggested to influence muscle mass and function, possibly by modification of microbiota composition, immune function, energy metabolism and oxidative stress [7,8]. However, studies on the effects of probiotics on muscle mass and function have been scarcely reported, and the potential effects of probiotics on physical performance and their underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, if several studies in animals indicate the possibility of a gut-muscle axis, it is important to outline that the reverse signaling from the muscle to the gut might also occur. Indeed, microbes develop a symbiontic reaction with their host and, consequently, reduced physical activity in sarcopenic subjects may be associated with different microbiota composition and metabolism [211,212]. This last point might be considered when the physical performance is measured in humans by gait speed test, because gut bacteria synthesize neurotransmitters such as serotonin, norepinephrine, GABA, or dopamine are able to influence the neurological control of movement [213].…”
Section: The Emerging Concept Of the Gut-muscle Axis-role Of Exercisementioning
confidence: 99%